Factors Impacting Employeeâs Satisfaction and Commitment in Banking Industry in Surabaya - Junius, Ivan (iBuss Management, 2015)
This research is done to know whether or not motivational factorsÂ  âÂ  consists of rewards, working conditions, managerial abilities, employee participation, company policies, recognition and feedback, as well as job interest and importanceÂ  âÂ  simultaneously and individually have impact on the satisfaction level and commitment level of banking industry employees in Surabaya. Multiple regressions were used as the analysis technique to reveal the relationship between them. The results show that Motivational Factors simultaneously have impact on both employeeâs satisfaction and commitment level, while job interest and importance was found to be the only factor that individually have impact on the satisfaction and the commitment level of banking industry employees in Surabaya.Keywords:Â  Motivational Factors, Employeeâs Satisfaction, Employeeâs Commitment, Banking Industry